Trackable Supramolecular Fusion: Cage to Cage Transformation of Tetraphenylethylene‐Based Metalloassemblies. (25th February 2020) - Li, Guangfeng; Zhou, Zhixuan; Yuan, Chang; Guo, Zhewen; Liu, Yuhang; Zhao, Dong; Liu, Kai; Zhao, Jun; Tan, Hongwei; Yan, Xuzhou
Abstract: Herein, the trackable supramolecular transformation of a two‐component molecular cage to a three‐component cage through supramolecular fusion with another two‐component molecular square is described. The use of tetraphenylethene (TPE), a chromophore with aggregation‐induced emission (AIE) character, as a component for the molecular cages enables facile fluorescence monitoring of the transformation process: while both cages exhibit fluorescence emission via the restriction of intramolecular motion of the TPE motif, the interactions between TPE and 4, 4′‐bipyridine introduced in the supramolecular fusion process result in partial fluorescence quenching and shifts in the emission maximum. This study provides a simple and efficient approach towards complex supramolecular cages with emergent functions and demonstrates that AIE features could provide unique opportunities for the characterization of complex, dynamic supramolecular transformation processes. Abstract : Ein Käfig voller Platin : Inspiriert von natürlichen Systemen wurde eine nachverfolgbare supramolekulare Platin(II)‐Käfig‐zu‐Käfig‐Umwandlung entwickelt. Sie nutzt programmierbare Metallkoordinationschemie sowie die einzigartigen photophysikalischen Eigenschaften AIE‐aktiver Metallanordnungen. AIE=aggregationsinduzierte Emission.